Isolation of Host-Dependent and Nonparasitic Mutants of the Facultative Parasitic Bdellovibrio UKi2 - Varon, Mazal (1974)
Obligate host-dependent and nonparasitic mutants were isolated from a facultative parasitic Bdellovibrio strain. Thus it is possible to separate host-dependency from the ability to parasitize in bdellovibrios.